2020
DOI: 10.1152/ajpgi.00301.2019
|View full text |Cite|
|
Sign up to set email alerts
|

Intestine-specific deletion of metal transporter Zip14 (Slc39a14) causes brain manganese overload and locomotor defects of manganism

Abstract: Impaired manganese (Mn) homeostasis can result in excess Mn accumulation in specific brain regions and neuropathology. Maintaining Mn homeostasis and detoxification is dependent on effective Mn elimination. Specific metal transporters control Mn homeostasis. Human carriers of mutations in the metal transporter ZIP14 and whole body Zip14-knockout (WB-KO) mice display similar phenotypes, including spontaneous systemic and brain Mn overload and motor dysfunction. Initially, it was believed that Mn accumulation du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…To determine the physiological relevance of these findings, intestine-specific Zip14 knockout mice (Zip14-In-KO) were generated. In contrast to Zip14-L-KO mice that did not develop manganese overload in the body, Zip14-In-KO mice developed increased manganese in both the liver and brain under normal dietary conditions, verifying the importance of intestinal ZIP14 in maintaining systemic manganese homeostasis [66,67]. Based on the results from these most recent studies, we propose a new model for the function of ZIP14 in regulating systemic manganese homeostasis that includes the functions of intestinal ZIP14 to limit dietary manganese absorption and hepatic ZIP14 to clear manganese from the portal blood (Figure 2A,B).…”
Section: The Molecular Mechanism Underlying Zip14 Deficiency and Mangmentioning
confidence: 90%
“…To determine the physiological relevance of these findings, intestine-specific Zip14 knockout mice (Zip14-In-KO) were generated. In contrast to Zip14-L-KO mice that did not develop manganese overload in the body, Zip14-In-KO mice developed increased manganese in both the liver and brain under normal dietary conditions, verifying the importance of intestinal ZIP14 in maintaining systemic manganese homeostasis [66,67]. Based on the results from these most recent studies, we propose a new model for the function of ZIP14 in regulating systemic manganese homeostasis that includes the functions of intestinal ZIP14 to limit dietary manganese absorption and hepatic ZIP14 to clear manganese from the portal blood (Figure 2A,B).…”
Section: The Molecular Mechanism Underlying Zip14 Deficiency and Mangmentioning
confidence: 90%
“…It has been proposed that modulation of ZIP14 may be involved in prevention of Mn-induced neurotoxicity [ 34 ]. A study in intestine-specific ZIP14-KO demonstrated that intestinal ZIP14 deficiency is responsible for systemic and brain Mn accumulation upon overexposure and cannot be compensated by hepatobiliary metal excretion [ 35 ]. ZIP14 deficiency in ZIP14 knock-out (KO) mice resulted in reduced Mn excretion after subcutaneous Mn administration as well as increased cerebral Mn accumulation with subsequent motor dysfunction [ 34 ].…”
Section: Manganese Transportersmentioning
confidence: 99%
“…In addition to the hepatobiliary excretion route, the intestinal absorption also plays important role in regulating the systemic manganese homeostasis [8,27]. Previous studies have demonstrated that, differently from Zip14-L-KO mice that did not develop systemic manganese overload, Zip14-In-KO mice had increased manganese in both the liver and brain under normal dietary conditions [15,16], suggesting that lack-of-ZIP14 increases intestinal manganese absorption [15]. Therefore, we next sought to determine whether limiting manganese intake can prevent the development of manganese overload in Zip14 −/− mice.…”
Section: Maternal Milk Manganese Level Can Be Altered By Dietary Interventionmentioning
confidence: 99%
“…However, even with reduced manganese uptake into the liver, Zip14-L-KO mice had normal manganese levels in the blood and other body tissues, suggesting that hepatic ZIP14 is not the primary control for systemic manganese homeostasis at physiological conditions [13,15]. In contrast to Zip14-L-KO mice that did not develop manganese overload in the body, mice with intestinal specific Zip14 knockout (Zip14-In-KO) developed increased manganese in both the liver and brain under normal dietary conditions, highlighting the importance of intestinal ZIP14 in maintaining systemic manganese homeostasis [15,16]. Taken together, these previous studies have confirmed an indispensable role for ZIP14 in regulating manganese homeostasis, because lack of ZIP14 leads to increased manganese absorption through the intestine [15] and impaired manganese clearance through hepatobiliary excretion [10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%